Local and global messages for prompting energy conservation behaviour: an experimental study in university - Wee, Siaw Chui (Penerbit UTM Press, 2015)
To create a cost effective environment during the management of building facilities, energy conservation is important among building users as it can help to conserve energy and reduce energy cost. To promote energy conservation, the behavior of user should be focused where their behavior should be improved to reduce energy wastage. Prompt is among the simplest and inexpensive behavioural interventions to improve energy conservation behavior. The prompt has been used wisely in healthcare sectors to promote healthy lifestyles, but no recent study on energy conservation behavior. The aim of this research was to investigate the effectiveness of prompt in prompting energy conservation behavior among the building users in university. An experiment was designed and carried out to examine the effectiveness of local and global types prompt messages for prompting efficiency use of energy. This research findings show that there was no significant difference between local and global types prompt messages, however, the findings indicate that both prompt messages were able to prompt the behavior change among the energy users and local type prompt message was more able to prompt the users than global types prompt messages. This finding could provide the useful information to society nowadays on using prompt to manage the energy efficiently.